2005
DOI: 10.1515/arbi.2005.14
|View full text |Cite
|
Sign up to set email alerts
|

Rüdiger Zymner, Gattungstheorie. Probleme und Positionen der Literaturwissenschaft. 2003

Abstract: Was hier unter dem anspruchsvollen und hohe Erwartungen weckenden Titel daherkommt, ist eine Einführung in die Problematik der Definition von Gattungen für Studierende und nicht etwa, was der Titel erwarten läßt, eine Theorie der literarischen Gattungen. Unter dem Gesichtspunkt des Zielpublikums soll das Buch rezensiert werden, denn als Beitrag oder auch nur als Forschungsüberblick zum Problem der Gattung kann es nicht aufgefaßt werden, dafür läßt es zu viele Aspekte einer historisch fundierten oder kommunikat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Other studies have identified stereotypical recurrent patterns in specific genres, such as crime fiction (Todorov, 1978;François, 2009;Lits, 2011), with the goal of developing a typology of literary genres. Despite such efforts, genre theory as a whole has tended to rely first and foremost on content-based features, privileging thematic and macrostructural aspects rather than linguistic criteria in typologies of literary genres (for a discussion of approaches within genre theory, see Duff, 2000;Zymner, 2003;Frow, 2006;Monte & Philippe, 2014).…”
Section: Approaches To Phraseology and Idiomaticitymentioning
confidence: 99%
“…Other studies have identified stereotypical recurrent patterns in specific genres, such as crime fiction (Todorov, 1978;François, 2009;Lits, 2011), with the goal of developing a typology of literary genres. Despite such efforts, genre theory as a whole has tended to rely first and foremost on content-based features, privileging thematic and macrostructural aspects rather than linguistic criteria in typologies of literary genres (for a discussion of approaches within genre theory, see Duff, 2000;Zymner, 2003;Frow, 2006;Monte & Philippe, 2014).…”
Section: Approaches To Phraseology and Idiomaticitymentioning
confidence: 99%